The plasma membrane redox system in human platelet functions and platelet-leukocyte interactions - Principe, Domenico Del; Frega, Gianluca; Savini, Isabella; Catani, Valeria M.; Rossi, Antonello; Avigliano, Luciana (Thrombosis and Haemostasis, 2009)
The plasma membrane electron transport is crucial for blood coagulation and thrombosis, since reactive oxygen species and thiol changes, generated by plasma membrane redox reactions, modulate activation of platelets, as well as their interaction with leukocytes. Several antioxidants are linked to this system; thus, platelets are also able to counterbalance radical production and to regulate thrombus growth. Aim of this review is to give an update on the plasma membrane redox system in platelets, as well as on its role in platelet functions and leukocyte-platelet crosstalk.
Keywords: Platelets; plasma membrane redox system; NAD(P)H oxidase; ubiquinone; antioxidant vitamins